An Investigation of the Self-Efficacy Levels of the Special Education Teachers Regarding Game Teaching - Kayhan, Nilay; Akmese, Pelin Pistav (ANKARA UNIV, 2017)
The game has been accepted as an effective teaching method which can be used in leaming period of the children in early childhood period. In this study, it has been aimed to investigate the self-efficacy of the special education teachers regarding game teaching with regard to self-efficacy of planning, application and assessment and career self-efficacy. In the study which was planned according to descriptive survey method, "Personal Information Form" and "Game Teaching Self-Efficacy Survey in Preschool Period" developed by Kadim (2012) were used. 127 special education teachers participated in the research. It has been found out that the self-efficacy levels of the teachers regarding game teaching do not differ, but there is a statistically significant difference between planning, application and assessment of game activities and game teaching career, self-efficacy levels and game total points in accordance with their alma mater, status of taking game teaching course and professional seniority. The educational status of the teachers generates a statistically significant difference on game teaching total points and their sex generates a in the sub-dimension of the game activity application. This study in which the game self-efficacy of special education teachers was? investigated is important to determine to what extend the teachers use the games as a teaching tool.
Keywords: Special education teachers; self-efficacy; game teaching